A Systematic Review of Attentional Focus Strategies in Weightlifting - Neumann, David L. (Frontiers in Sports and Active Living, 2019)
The way an athlete focuses their attention when lifting a weight has the potential to influence strength development during training and performance outcomes during competition. The effects of attentional focus strategies during weightlifting tasks was investigated through a systematic review. Major databases (SportDISCUS, PsycINFO, Scopus) were searched using key terms relevant to attentional focus and weightlifting and reference lists of identified articles were also searched. Following screening, 16 articles were retained for analysis. The review showed that researchers have recruited experienced and novice weightlifters of both genders in their studies, although male experienced weightlifters are the most commonly studied demographic. Weightlifting tasks have varied from bench press, biceps curls, squats, and leg extensions with some studies using measures of force production against a force plate. The predominant manipulations of attentional focus have been between internal-associative and external-associative foci. An external attentional focus has shown to be beneficial in terms of movement economy as reflected in a variety of outcome measures. The results are interpreted within the framework provided by the Constrained Action Hypothesis and more generally the advantages of an external attentional focus for motor skill learning. An external focus of attention promotes automatic control of actions, thus preventing the motor system being constrained by conscious cognitive control. Implications for informing training programs for athletes and for advising athletes to maximise performance during competition are discussed.